On equilibrium charge distribution above dielectric surface - Lytvynenko, D.M.; Slyusarenko, Yu.V. (Condensed Matter Physics, 2009)
The problem of the equilibrium state of the charged many-particle system above dielectric surface is formulated.
We consider the case of the presence of the external attractive pressing field and the case of its
absence. The equilibrium distributions of charges and the electric field, which is generated by these charges
in the system in the case of ideally plane dielectric surface, are obtained. The solution of electrostatic equations
of the system under consideration in case of small spatial heterogeneities caused by the dielectric surface,
is also obtained. These spatial inhomogeneities can be caused both by the inhomogeneities of the surface
and by the inhomogeneous charge distribution upon it. In particular, the case of the wavy spatially periodic
surface is considered taking into account the possible presence of the surface charges. Сформульовано задачу про рiвноважний стан системи багатьох заряджених частинок над поверхнею дiелектрику як у присутностi зовнiшнього притягувального електричного поля, так i при його вiдсутностi. Отримано рiвноважнi розподiли зарядiв та електричного поля, що виникає завдяки цим зарядам, у випадку iдеально плоскої поверхнi дiелектрику. Також отриманi розв’язки рiвнянь електростатики для дослiджуванної системи у випадку малих просторових неоднорiдностей, пов’язаних iз поверхнею дiелектрику. Вiдмiченi просторовi неоднорiдностi можуть бути пов’язанi як iз неоднорiдностями самої поверхнi, так i з неоднорiдним розподiлом заряду на нiй. Розглянуто також випадок хвилястої, зокрема, просторово-перiодичної поверхнi з урахуванням можливостi iснування на нiй просторових зарядiв.